2005
DOI: 10.1038/ng1508
|View full text |Cite
|
Sign up to set email alerts
|

A common inversion under selection in Europeans

Abstract: A refined physical map of chromosome 17q21.31 uncovered a 900-kb inversion polymorphism. Chromosomes with the inverted segment in different orientations represent two distinct lineages, H1 and H2, that have diverged for as much as 3 million years and show no evidence of having recombined. The H2 lineage is rare in Africans, almost absent in East Asians but found at a frequency of 20% in Europeans, in whom the haplotype structure is indicative of a history of positive selection. Here we show that the H2 lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
807
4
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 752 publications
(852 citation statements)
references
References 42 publications
37
807
4
4
Order By: Relevance
“…10,11 Most fall into two genetically distinct haplotypes: the H1 haplotype, which is most common, and the inverted H2 haplotype, which is present at a frequency of~20% in European chromosomes. 12 We previously showed that there is a H2 predisposition to the microdeletion, 13 which can be explained by the fact that the most prevalent H2 haplotype contains homologous segmental duplications in direct orientation flanking the diseasecritical region, whereas no such sequence is observed in the H1 haplotype. 10,11,14 Itsara et al 15 showed that the 17q21.31 deletion breakpoints reside within the flanking homologous sequences and that the deletion can be mediated by intrachromosomal non-allelic homologous recombination involving the H2-specific LCRs in direct orientation or by an interchromosomal unequal crossover between the H1 and H2 haplotypes.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Most fall into two genetically distinct haplotypes: the H1 haplotype, which is most common, and the inverted H2 haplotype, which is present at a frequency of~20% in European chromosomes. 12 We previously showed that there is a H2 predisposition to the microdeletion, 13 which can be explained by the fact that the most prevalent H2 haplotype contains homologous segmental duplications in direct orientation flanking the diseasecritical region, whereas no such sequence is observed in the H1 haplotype. 10,11,14 Itsara et al 15 showed that the 17q21.31 deletion breakpoints reside within the flanking homologous sequences and that the deletion can be mediated by intrachromosomal non-allelic homologous recombination involving the H2-specific LCRs in direct orientation or by an interchromosomal unequal crossover between the H1 and H2 haplotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Subtle effects of the inversion may, however, have escaped detection. A notable example is the 900 kb submicroscopic inversion polymorphism of chromosome 17q21.31 recently analyzed in different populations [Stefansson et al, 2005]. Epidemiological studies suggest that this inversion is under positive selection.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a specific but subtle effect mediated by an inversion may become clear only in a longer perspective and detected from the analysis of large and ethnically diverse populations [Stefansson et al, 2005]. In a broader context, inversions are thought to be key players in evolution and account for much of the genomic differences between humans and other primates [Iafrate et al, 2004;Sebat et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…70 Association studies of this type harbor great potential for complex disorders, but a number of very important challenges, including how to interpret results obtained from large numbers of statistical tests, and how to detect biologically meaningful interactions between polymorphisms that confer disease risk, will need to be overcome. Furthermore, to correctly interpret large-scale SNP data we must discern to what extent the SNPs under analysis are located within segmental duplications, 71 inversions, 72 or regions with loss of imprinting, 73 polymorphic genomic imbalances, 74 or resistant to X-inactivation. 75 Genetic heterogeneity in MS A noteworthy conceptual development in the understanding of MS genetics has been the recognition of locus heterogeneity, meaning that different genes can cause identical or similar forms of the disease in different individuals.…”
Section: Rr-ms Sp-msmentioning
confidence: 99%